Improving indirect measurements of the leaf area index using canopy height - Gonçalves, Alexandre Ortega; Silva, Evandro Henrique Figueiredo Moura da; Gasparotto, Letícia Gonçalves; Rosa, Juliano Mantelatto; Carmo, Stephanie do; Fattori Júnior, Izael Martins; Marin, Fábio Ricardo (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the use of plant height as a calibration variable for improving indirect measurements of the leaf area index (LAI). Three experiments were conducted with different crops – corn (Zea mays), soybean (Glycine max), and sugarcane (Saccharum officinarum) –, to compare the performance of the LAI measured indirectly (LAIind) and corrected by the calibration variable with the LAI measured directly (LAIref). Without the proposed correction, the LAIind tended to be overestimated by 20%, on average, compared with the LAIref, for the three crops. After crop height was used to adjust the LAIind, a strong positive relationship was observed between the LAIref and the corrected LAIind (R2 = 0.96); overestimation was reduced to 4% and the mean square error decreased to 0.07 m2 m-2. The variable canopy height is promising for the correction of the LAI of the soybean, corn, and sugarcane crops.